Influence of city on the floristical and ecological diversity of Bryophytes in parks and cemeteries - Fudali, Ewa (Biodiversity: Research and Conservation, 2006)
This paper presents some of the results of studies on bryophyte species richness, diversity and ecology in the 94 parks and 51 cemeteries of six Polish cities: Warsaw, Cracow, Wrocław, Poznań, Lublin and Szczecin. The total number of species recorded in these 145 sites was 125; made up of 11 liverwort and 114 moss taxa. The number of species which occurred in individual sites was not significantly correlated with their area (R2=22%) or biotope type (R2=16%). The bryoflora of the parks and cemeteries studied appeared to be varied ecologically; only 30% of species were eurytopic. Both city ubiquists and bryophyte species, ecologically specialized, never recorded in densely built-up urban areas occurred in the sites studied. Most of the city centre parks studied were poorer in bryophyte species than those on the outskirts, although not all of the latter were necessarily species rich.